Evaluation of Compressive Strength of Concrete Using Stone Dust and Superplasticizer - Chhetri, Yudip Subedi; Joshi, Buddhi Raj; Bhandari, Chakra; Aryal, Rajendra; Adhikari, Prakash Bahadur; KC, Narayan; Banjara, Santosh (Technical Journal, 2024)
Concrete, which is usually composed of cement, water, and fine and coarse aggregate, is the most dynamic building material for the construction of physical infrastructures because of its strength and durability, which solidifies over time in response to environmental changes. The size and shape of the aggregate have a significant impact on workability, strength, and durability of concrete since various particle sizes produce distinct reactions. To support the manufacturing of sustainable concrete, the research suggested substituting stone dust (SD) for sand. In contrast to the addition of stone dust, the application of superplasticizers improves the workability of concrete. The study aims to examine the compressive strength of M20-grade concrete that has superplasticizer added in addition to stone dust as fine aggregate replacement. The Maximum compressive strength of concrete has been achieved at 40% sand replacement. The findings revealed that the increase in stone dust content results in an increase in compressive strength of concrete using superplasticizer. The use of superplasticizer serves to increase the workability of the concrete and has no discernible effect on the compressive strength up to 50% sand replacement. The 28-days compressive strength achieved maximum value at 50% sand replacement with 2% superplasticizer. When stone dust and superplasticizer are added, the concrete becomes denser; conversely, when the amount of stone dust and superplasticizer is increased, the concrete becomes more slumped. For the construction of sustainable concrete, the SD can be used in place of fine aggregate in conjunction with superplasticizer.